A Community-Based Feasibility Study of Weight-Loss in Rural, Older Adults with Obesity. Issue 3 (1st October 2020) - Batsis, John A.; Petersen, Curtis L.; Cook, Summer B.; Al-Nimr, Rima I.; Pidgeon, Dawna; Mackenzie, Todd A.; Bartels, Stephen J.
Abstract: This study was a 12-week feasibility weight-loss intervention consisting of caloric restriction and aerobic/resistance exercise in older adults with obesity (body mass index ≥ 30 kg/m 2 ) in a geographically isolated area. Primary outcomes assessed weight and physical function. Mean age was 71.0 ± 5.1 years (67% female). Individuals completed 100% of all assessments, attended 88% of the physical therapy classes and 89% of the nutrition sessions. Level of satisfaction (5-point Likert) was high (5.0, 1 – low; 5 – high). Weight decreased from 93.7 ± 9.7 to 89.4 ± 4.0 kg ( p < 0.001). Mean BMI and waist circumference decreased, respectively, from 35.4 ± 3.4 to 33.6 ± 3.7 ( p < 0.001), and 116.3 ± 7.5 to 108.7 ± 9.2 cm ( p = 0.002). Grip strength, gait speed, and 5-times sit-to-stand time all improved from 29.2 ± 7.5 to 35.2 ± 6.7 kg ( p = 0.006), 1.16 ± 0.21 to 1.35 ± 0.23 m/s ( p = 0.004), and 12.5 ± 4.0 to 9.6 ± 1.7s ( p = 0.02). The intervention was feasible and acceptable, and holds promise in promoting weight loss with a concomitant improvement in physical function in older adults.